IGF2BP3 promotes progression of gallbladder carcinoma by stabilizing KLK5 mRNA in N6-methyladenosine-dependent binding - Zhang, Junzhe; Yang, Kaini; Bu, Junfeng; Yan, Jiayan; Hu, Xiaoqiang; Liu, Ke; Gao, Si; Tang, Shuibin; Gao, Lili; Chen, Wei (Frontiers in Oncology, 2022)
Background: Recent studies reported that IGF2BP3 has been linked to the pathogenesis of various malignancies. As IGF2BP3 is associated with poor outcome of gallbladder carcinoma (GBC), we aimed to explore the N6-methyladenosine (m6A) RNA methylation function of IGF2BP3 in regulating GBC progression. Methods: Bioinformatic analysis of GSE136982, GSE104165, and RNA-seq was performed. In vitro and in vivo gain- and loss-of-function assays were done. qPCR, western blotting, and IHC were conducted in cells or collected clinical tissues. RNA immunoprecipitation, RNA stability measurement, methylated RNA immunoprecipitation, and dual-luciferase reporter assays were performed in this study. Results: The expression of IGF2BP3 was higher in GBC tissues than in peritumoral tissues. Functionally, cell proliferation and migration in vitro and in vivo were inhibited by downregulation of IGF2BP3. The analysis of RNA-seq indicated that KLK5 was a downstream target of IGF2BP3. The expression of KLK5 was measured in GBC cells and tumor samples. It was positively correlated with IGF2BP3 level. After IGF2BP3 depletion, ectopic expression of KLK5 partly rescued cell function. Mechanistically, we found that IGF2BP3 directly binds KLK5 mRNA and regulates its stability in an m6A-dependent manner. As a result, inhibition of KLK5 decreased the expression of PAR2, and deregulated AKT1 pathway. By bioinformatic prediction combined with miRNA microarray analysis, we identified that let-7g-5p is an inhibitor of IGF2BP3, and let-7g-5p expression was negatively correlated with IGF2BP3. Overexpression of let-7g-5p affected the aggressive phenotype of GBC cells via deregulating IGF2BP3, and inhibiting KLK5/PAR2/AKT axis. Conclusions: Our data showed that IGF2BP3 is associated with the aggressive phenotype of GBC. Mechanistically, IGF2BP3 activated PAR2/AKT axis by stabilizing KLK5 mRNA in an m6A-dependent. The loss of let-7g-5p enhanced the expression of IGF2BP3 and GBC progression. Thus, IGF2BP3 plays a crucial role in GBC, and let-7g-5p/IGF2BP3/KLK5/PAR2 axis may be a therapeutic target for GBC.